DEVELOPMENT OF THE CAPITAL CITY NUSANTARA BASED ON PANCASILA AND THE NUSANTARA PERSPECTIVE - Budi Kalimantoro; K.P. Suharyono S. Hadiningrat (JIPOWER : Journal of Intellectual Power, 2024)
The annexation of the Sipadan and Ligitan islands by neighboring countries and the loss of East Timor serves as a crucial lesson and warning for all components of the nation to rise together to defend the territory and sovereignty of the Unitary State of the Republic of Indonesia to the last drop of blood. The government must continue the struggle for independence, which has now lasted for 79 years, through equitable, fair, and prosperous development, including the development of the capital city Nusantara in accordance with Law No. 3 of 2022 regarding the Capital City and its amendments. This research design is descriptive qualitative, analyzing data on the variables of capital city development, Pancasila values, and the Nusantara Perspective to uncover and describe the phenomena of these variables narratively (non-numeric). The development of the Capital City Nusantara, which is currently underway, is expected to become a sustainable global city built as a manifestation of Pancasila values and the Nusantara Perspective. The development of IKN Nusantara is an integral part of national development and is expected to become a global city for all, built and managed with the following objectives:a) to become a sustainable city globally; b) as the driving force of Indonesia’s future economy; and c) to become a symbol of national identity representing the diversity of the Indonesian nation, based on Pancasila and the 1945 Constitution of the Republic of Indonesia. It is recommended that the Central Government and IKN Authority truly carry out the development of IKN Nusantara for national interests and manifest the values of Pancasila and the Nusantara Perspective.